2018
DOI: 10.1242/bio.032425
|View full text |Cite
|
Sign up to set email alerts
|

Sustained exercise-trained juvenile black carp (Mylopharyngodon piceus) at a moderate water velocity exhibit improved aerobic swimming performance and increased postprandial metabolic responses

Abstract: The objectives of this study were to examine whether sustained exercise training at four water velocities, i.e. nearly still water (control), 1 body length (BL) s−1, 2 BL s−1 and 4 BL s−1, has effects on swimming performance and digestive metabolism in juvenile black carp (Mylopharyngodon piceus). The results demonstrated that fish subjected to sustained training at 2 and 4 BL s−1 showed significantly higher critical swimming speed (Ucrit) and maximum metabolic rate (MMR) over the control group. Fish subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Numerous studies have found that appropriate continuous aerobic training can improve the critical swimming speed of many fish, such as common carp [21] trained at 60% U crit speed for 28 days, black carp (Mylopharyngodon piceus) [44] trained at 2 and 4 bl s −1 water velocity for 8 weeks and bream [6] trained at 4 bl s −1 water velocity for 5 weeks. However, this study found that U crit was not significantly different among the control and training groups.…”
Section: Effect Of Aerobic Training On Swimming Performancementioning
confidence: 99%
“…Numerous studies have found that appropriate continuous aerobic training can improve the critical swimming speed of many fish, such as common carp [21] trained at 60% U crit speed for 28 days, black carp (Mylopharyngodon piceus) [44] trained at 2 and 4 bl s −1 water velocity for 8 weeks and bream [6] trained at 4 bl s −1 water velocity for 5 weeks. However, this study found that U crit was not significantly different among the control and training groups.…”
Section: Effect Of Aerobic Training On Swimming Performancementioning
confidence: 99%
“…To date, whether continuous flow stimulation always can improve the aerobic exercise performance (e.g., U crit ) of fish remains controversial and is mainly dependent on the fish species (Davison, 1997; Hou et al, 2022; Li, Pang, et al, 2017; Li et al, 2018; Lu et al, 2020). Some studies found that continuous flow stimulation failed to promote the U crit of fish species, such as leopard shark ( Triakis semifasciata ), chinook salmon ( Oncorhynchus tshawytscha ) and rock carp (Gallaugher et al, 2001; Gruber & Dickson, 1997; Hou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that continuous flow stimulation failed to promote the U crit of fish species, such as leopard shark ( Triakis semifasciata ), chinook salmon ( Oncorhynchus tshawytscha ) and rock carp (Gallaugher et al, 2001; Gruber & Dickson, 1997; Hou et al, 2022). However, improved U crit has also been observed in many fish subjected to continuous flow stimulation, such as the striped bass ( Morone saxatilis ), qingbo, common carp ( Cyprinus carpio ), bream ( Megalobrama pellegrini ), black carp ( Mylopharyngodon piceus ) and Prenant's schizothoracin (He et al, 2013; Li, Pang, et al, 2017; Li et al, 2018; Lu et al, 2020; Young & Cech, 1993; Zhao et al, 2012). In this study, the U crit s of 2 and 4 bl s −1 flow groups increased significantly by 20% and 14% respectively, compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is no general consensus as to the effects of flow velocity on the swimming and metabolism of fish species. Many of the apparent discrepancies are generally caused by differences in the fish species chosen and the regime of flow rate utilized [35,36] . Therefore, the internal mechanisms that produced the results in this study have to be explored in depth.…”
Section: Table 3 Coefficients Of Ammonia Excretion Model At Different...mentioning
confidence: 99%